Usulan Kebijakan Logistik Pengelolaan Sampah di Kota Padang: Lessons Learnt Penentuan Lokasi dan Rute Pengangkutan Sampah - Rika Ampuh Hadiguna; Sabda Alfath (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2015)
Waste management should keep material and information flows as a whole. Connectivity both these streams become a waste logistics network. In Padang, In Padang, The Garbage Collection Location (TPS) is not optimal connectivity in a transportation system that affect the pattern of transporting waste to landfill (TPA). The purpose of this study is to propose the design of waste logistics network policy, namely: determining the TPS location in every village and determine the transport route transporting waste from TPS to the landfill. Analytical Hierarchy Process (AHP) is applied as the method used to select the location of the polling stations and waste transportation route determination using the Vehicle Routing Problem (VRP) for the route from TPS to TPA. Sstudy results was a model waste management logistics policy at the operational level, tactical and strategic simultaneously. At the operational level, this study has proposed to build a mathematical formulation to determine transportation from the TPS location to the TPA landfill. Tactical policy level is to determine number of trucks, while the strategic policy is proposed locations of TPA with the cluster approach service areas.